A Sheltered High: Creating a safe space for drug consumption in Durban Central - Ndima, Similo (My University, 2019)
South Africa has become one of the drug capitals of the world and according to the World Health Organization in 2015 an estimated 15% of the population were involved in drug abuse. The current economic situation in the country resulting in high unemployment has seen these numbers rapidly increasing from year to year. As one of the main import points of drugs in the country, Durban has a high number of addicts in the city, who use spaces such as public parks, dilapidated buildings and railway tracks to consume their desired substances. While substances like alcohol and cigarettes have been provided spaces like bars and smoking areas for their consumption, people addicted to ‘harder’ drugs have no such spaces and are forced to use public spaces in the city. This research proposes designing an urban scheme in Durban Central which turns the city into a place where addiction is accepted as a common phenomenon and help can be provided to those that desire it, while accepting those still struggling with addiction. Decriminalizing drug usage and providing space for drug consumption to take place safely in spaces like injection facilities is a strategy that has been used all over Europe. This thesis will propose introducing similar facilities in a South African context to help reduce drug related crime and protect both drug addicts and others in the city from harm, while relying on rehabilitation clinics for longer term solutions. Zones like back-alley ways, bridge overpasses and abandoned buildings, are seen as unintentional, misused or forgotten spaces and have therefore become a retreat for substance abusers avoiding the eyes of the law. These zones have often been adopted by the drug-addicts to the point where these zones now have a defined function. The architectural approach of this thesis is to re-appropriate the leftover spaces in the city and create a building which becomes a beacon that looks to bring light to underground drug culture in the city and heal through acceptance.